Styrene–butadiene–styrene-based stretchable electrospun nanofibers by carbon nanotube inclusion - Sarac, Baran; Gürbüz, Remzi; Micusik, Matej; Omastova, Maria; Rezvan, Amir; Yüce, Eray; Xi, Lixia; Eckert, Jürgen; Ozcan, Ali; Sarac, A. Sezai (Royal Society of Chemistry (RSC), 2023)
The state-of-the-art organic composite nanofibers have advantages due to their low cost, mechanical flexibility, light weight and electrical conductivity. Crystalline-to-amorphous transition and carbon-oxygen interactions are observed with addition of carbon nanotubes.